SIM imaging resolves endocytosis of SARS-CoV-2 spike RBD in living cells. Issue 3 (16th March 2023) - Miao, Lu; Yan, Chunyu; Chen, Yingzhu; Zhou, Wei; Zhou, Xuelian; Qiao, Qinglong; Xu, Zhaochao
Summary: It is urgent to understand the infection mechanism of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for the prevention and treatment of COVID-19. The infection of SARS-CoV-2 starts when the receptor-binding domain (RBD) of viral spike protein binds to angiotensin-converting enzyme 2 (ACE2) of the host cell, but the endocytosis details after this binding are not clear. Here, RBD and ACE2 were genetically coded and labeled with organic dyes to track RBD endocytosis in living cells. The photostable dyes enable long-term structured illumination microscopy (SIM) imaging and to quantify RBD-ACE2 binding (RAB) by the intensity ratio of RBD/ACE2 fluorescence. We resolved RAB endocytosis in living cells, including RBD-ACE2 recognition, cofactor-regulated membrane internalization, RAB-bearing vesicle formation and transport, RAB degradation, and downregulation of ACE2. The RAB was found to activate the RBD internalization. After vesicles were transported and matured within cells, RAB was finally degraded after being taken up by lysosomes. This strategy is a promising tool to understand the infection mechanism of SARS-CoV-2. Graphical abstract: Highlights: RBD endocytosis is resolved by imaging the location and ratio of ACE2/RBD fluorescence Exploring the initiation and influencing factors of RBD internalization The movement and maturation of ACE2/RBD co-localized vesicles are tracked by SIM imaging The RBD-ACE2 complex is taken up and degraded by lysosomes Abstract : Miao et al. genetically encoded RBD and ACE2 with Halo/SNAP tags and then labeled them with rhodamine/cyanine dyes. SIM imaging resolved endocytosis of RBD-ACE2 binding in living cells, including RBD-ACE2 recognition on the plasma membrane, cofactor-regulated membrane internalization, RAB-bearing vesicle formation and transport, RAB degradation, and downregulation of ACE2.